Seismic loss assessment of a structure retrofitted with slit-friction hybrid dampers. (1st January 2017) - Kim, Jinkoo; Shin, Hyungjun
Highlights: A hybrid damper is developed by combining a steel slit plate and friction pads. Its effectiveness is investigated by cyclic test and by loss estimation. The life cycle costs are computed based on FEMA P-58 methodology. The hybrid damper turns out to be more effective than slit dampers with the same yield strength. Abstract: In this study a hybrid energy dissipation device is developed by combining a steel slit plate and friction pads to be used for seismic retrofit of structures, and its effectiveness is investigated by comparing the life cycle costs of the structure before and after the retrofit. A hybrid damper is manufactured and is tested under cyclic loading. It is observed that the damper shows stable hysteretic behavior throughout the loading history, and that the cumulative ductility ratio obtained from the experiment far exceeds the limit value required by the AISC Seismic Provisions. The probabilities of reaching various damage states are obtained by fragility analysis to evaluate the margin for safety against earthquakes, and the life cycle costs of the model structures are computed using the PACT (Performance Assessment Calculation Tool). According to the analysis results the slit-friction hybrid damper shows superior performance to the slit damper with the same yield strength for seismic retrofit of structures. The analysis results also show that the probabilities of reaching the limit states are minimized by the seismic retrofit with hybrid dampers combined with increasing column size. The combined seismic retrofit method also results in the lowest repair cost and shortest repair time.